A smooth tool path generation and real-time interpolation algorithm based on B-spline curves. (January 2018) - Sun, Shujie; Yu, Dong; Wang, Changhui; Xie, Chuanning
In the machining progress of free-form surface, tool path is presented as continuous small line segments. To achieve high machining speed and fine machining quality, the tool path needs to be smoothed. This study presents a smooth tool path generation algorithm based on B-spline curves for small line segments machining. The algorithm includes two modules: smooth tool path generation module and real-time look-ahead interpolation module. In the smooth tool path generation module, the tool path is divided into non-fitting regions and fitting regions by three conditions: the length of small line segments, the angle of adjacent small line segments, and the change rate of the length and angle. To control contour error and get fine machining quality, the fitting regions are corrected by circle correction method and fitted into B-spline curves, while the non-fitting regions are smoothed with B-spline curves. In this module, the gained tool path has continuous curvature. In the interpolation module, the seven-phase jerk-limited look-ahead planning is adopted to generate smooth machining velocity, while the calculation accuracy of interpolation point generated by the interpolation period crossing two adjacent tool path is controlled. Simulations and experimental results demonstrate that the proposed algorithm is able to reduce the amount of numerical control codes, achieve high machining speed, and improve machining quality.